2009
DOI: 10.1111/j.1475-3588.2008.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale to Assess the Attitudes of Paediatric Staff to Caring for Children with Medically Unexplained Symptoms: Implications for the Role of CAMHS in Paediatric Care

Abstract: Background:  Children with medically unexplained symptoms (MUS) represent a challenge for paediatricians and typically undergo extensive in‐patient investigations for symptoms such as abdominal pain. This can delay access to psychological services. This study aims to develop and evaluate a scale to assess the attitudes of paediatric staff to caring for children with MUS and to explore factors influencing those attitudes. Method:  In this cross‐sectional survey, 118 health professionals at one UK hospital with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…[9] Research shows that there is a significant relationship between somatization in children and adolescents and family conflicts, and the deterioration of family functionality is one of the reasons for somatization disorders. [4,10,11] Factors supporting somatization include the presence of physical diseases or disease behaviors in family members, early experiences in attracting interest and love when they were physically unwell, as well as secondary acquisitions. [12,13] Family system theoreticians suggested that the nature of family interactive patterns plays an important role in the etiology of somatic symptoms in children, as well as their development into a chronic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Research shows that there is a significant relationship between somatization in children and adolescents and family conflicts, and the deterioration of family functionality is one of the reasons for somatization disorders. [4,10,11] Factors supporting somatization include the presence of physical diseases or disease behaviors in family members, early experiences in attracting interest and love when they were physically unwell, as well as secondary acquisitions. [12,13] Family system theoreticians suggested that the nature of family interactive patterns plays an important role in the etiology of somatic symptoms in children, as well as their development into a chronic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of 128 paediatric HCPs working in one UK hospital, respondents reported feeling that children and young people with MUS have unmet support needs (Glazebrook et al . ). In subsequent qualitative interviews with 12 survey respondents, HCPs reported feeling ambivalent about current service provision.…”
Section: Resultsmentioning
confidence: 97%
“…There is some limited evidence to suggest that HCPs would like to receive further information and support from CAMHS to help them provide appropriate individualised support to families of children experiencing MUS (Glazebrook et al . ), although further research is required to ascertain whether this view is shared by professionals working in other health and social care settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study forms part of a larger study, in which 128 paediatric health professionals within a single UK Hospital Trust (50% response rate) completed questionnaires about their attitudes to MUPS care (Glazebrook, Furness, Tay, Abbas, & Slaveska-Hollis, 2009). Participants were invited to participate in focus groups or individual interviews to discuss their experiences and perceptions further.…”
Section: Design and Methodsmentioning
confidence: 99%